KOMUNIKASI BISNIS PEMASARAN ONLINE (Proses dan Strategi Pemasaran Online Bagi Pelaku Bisnis di Kota Kupang) - Yermia Djefri Manafe (Journal of Management Small and Medium Enterprises (SMEs), 2016)
Business communication which is built in the online shop-reaching not only limited tocorrespondence and advertising that are likely to be persuasive, but also cover all aspects. Businesscommunication is done between humans, humans with institutions and institutions with aninstitution related to the exchange of goods or services for profit. Business communications covers allaspects of "how to receive, express and exchange ideas in business". Business communicationincludes sending and receiving messages between people or within one or more environment with thepurpose of influencing behavior in an organization. This study was conducted to describe andunderstand the process of business communication and online shop branding strategy in order tomaintain customer confidence for businesses in the city of Kupang.Keywords : Communication, Business, Business Communication, Online Media, Online Business